PSYCHOPHYSIOLOGICAL PECULIARITIES OF ADOLESCENT ATHLETES OF DIFFERENT SPORTS SPECIALIZATION - Vedernikova, E.V.; Morozova, M.A.; Shushkanova, E.G.; Krotova, M.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the psychophysiological characteristics of adolescent athletes of various sports specializations. Methods and structure of the study. The scientific work was attended by 144 athletes involved in the sports sections of the city of Kirov: boxing, sambo, swimming, rugby and hockey. The psychophysiological status of young athletes was assessed using the psychophysiological testing device UPFT-1/30 - "Psychophysiologist". Based on the performed tests (tapping test, simple visual-motor reaction and reaction to a moving object), the functional state of the nervous system of the studied contingent was assessed. Results and conclusions. Most adolescent athletes (with the exception of swimmers) have low stability of reactions and, as a result, a low ability to regulate processes in the nervous system. An assessment of the values of the reaction to a moving object (RMO) showed that, judging by the balance coefficient in most of the children we studied, the processes of inhibition prevail over the processes of excitation. The exception was sambists, in whom excitation prevailed over inhibition, i.e. they had more lead reactions than lag reactions. Consequently, sambo classes develop a strategy of anticipation in young athletes. Thus, the specificity of practicing different sports not only imposes certain requirements on the psychophysiological state of a young athlete, but also, in turn, influences this state in one way or another.